Existe-t-il un rapport entre la psychanalyse et la politique. // Is there a relationship between psychoanalysis and politics. - Lina María Vélez. (Affectio Societatis, 2010)
This paper attempts to analyze the concept of segregation introduced and developed by Lacan between 1967 and 1970. Such concept appears in the intersection of three issues: social bond and politics, analytical institution and pass and, finally, discourse and science. Segregation is the very principle of all the discourses that structure human bonding. We try to analyze, on the one hand, the principle of segregation as a structural fact and integral part of mankind and, on the other hand, the segregation phenomena as a practice in contemporary social bonding. // Cet article se propose d’analyser la notion de ségrégation que Lacan introduit et déploie entre 1967 et 1970. Ce concept apparaît au croisement de trois problématiques: le lien social et la politique, l’institution analytique et la passe et finalement le discours de la science. La ségrégation est le principe même des discours qui structurent les liens humains. Il s’agit d’analyser d’une part le principe de ségrégation comme fait de structure et indissociable de l’humanité et d’autre part les phénomènes de ségrégation en tant que pratique dans le lien social contemporain.